Experimental and analytical study on impact response of stainless steel-aluminium foam-alloy steel sandwich panels - Liu, Kun; Kang, Shao-Bo; Gao, Shan (International journal of impact engineering, 2023)
•The impact resistance, failure pattern and energy absorption of stainless steel-aluminium foam-alloy steel sandwich panels under single and repeated impacts were investigated.•The effects of the thickness of the front sheet, back sheet and aluminium foam on the impact response of sandwich panels were examined.•An analytical model considering the back sheet deformation was proposed to predict the first peak force and associated displacement. This paper investigates the impact response of stainless steel-aluminium foam-alloy steel sandwich panels under single and repeated impacts. Fourteen specimens were tested under single and repeated impacts, in which the dynamic response, failure pattern and energy absorption capacity of sandwich panels were investigated. Test results showed that the thickness of the front sheet, back sheet and aluminium foam had significant influences on the bearing capacity and energy absorption capacity of sandwich panels. Comparisons were also made between sandwich panels subjected to single and repeated impacts. It was found that the impact response and failure pattern of sandwich panels under repeated impacts could be significantly different from that under a single impact, mainly due to the development of arc-shaped deformations near the direct impact region. A local indentation model is proposed for sandwich panels considering the deformation of the back sheet, which can predict the first peak force, associated displacement and energy absorption with reasonably good accuracy. It also demonstrates that compared with alloy steel, the energy absorption of sandwich panels with stainless steel as the front sheet is considerably improved. This study provides an important reference for the design of stainless steel-aluminium foam-alloy steel sandwich panels under impact loadings.